EYE OPTICS, PROPERTIES OF LIGHT, EYE REFRACTION AND ITS EXAMINATION METHODS (Лучшие интеллектуальные исследования, 2025)
Abstract: This article analyzes the basic concepts of the optical system of the eye and the physical properties of light for medical students. The main properties of light, such as reflection, refraction and scattering, as well as the optical structure of the eye, as well as physiological and optical phenomena in the process of vision, are considered in detail. This study serves to enrich medical students' knowledge of ophthalmology and optics.